One Step Hydrothermal Synthesis of Nickel Doped TiO2 Nanotube - Budi Nursanto, Eduardus; Sinaga, Resa Mayori Ridoi; Floresyona, Dita; Rachman, Rinaldi Medali; Nugroho, Agung (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
TiO2 is one of the photocatalyst materials that is widely used and proven for environmental treatment. To increase the activity of TiO2, TiO2 has been modified into a nanotube shape with nickel metal doping. The TiO2 nanotubes with Ni doping have been synthesized with one step hydrothermal process. In this research, it shows that nickel doped with TiO2 led to a reduction of crystal size and band gap energy. The smaller crystalline size and lower band gap energy enhanced its photocatalytic activity. The best results for photocatalytic activity were TiO2/Ni with a crystal size of 7.30 nm and a band gap energy value of 3.12 eV. The photocatalytic activity of TiO2/Ni was tested by degrading methylene blue under mercury lamp radiation, with the best result of 92.73 % degradation of methylene blue, within 240 minutes of photocatalytic activity.